Teknologi, Inovasi, dan Pertumbuhan Ekonomi Islam di Negara Muslim - Firla Azizah; Ival Fadliyanto; Julfie Zahara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the role of technology and innovation in supporting the growth of the Islamic economy in Muslim countries. The development of digital technology has brought significant changes to people's lives, particularly in economic activities. The presence of the internet, smartphones, and various digital platforms has made economic activities easier, faster, and more practical. This research shows that technology and innovation have a significant influence on the development of the Islamic economy. Technology helps people access Islamic economic services more easily and efficiently. Overall, technology and innovation play a crucial role in strengthening the growth of the Islamic economy in the digital era. Therefore, support from the government, financial institutions, the business community, and the public is needed to ensure that the use of technology in the Islamic economy can develop optimally and remain in accordance with Sharia values.